E-223 Clinical and angiographic results with the new generation surpass flow diverter, evolve: a single center real world experience. (4th August 2020) - Derakhshani, S; Lynch, J; Kanagarajah, L
Abstract : Objectiv: To share the angiographic and clinical outcome in 35 consecutive patients treated with new generation Surpass Evolve Flow Diverter in our institution by a single operator team. Methods: Thirty-five consecutive patients (70% women, average age 58 years), with anterior or posterior circulation aneurysms treated with Surpass Evolve FD in a single centre. Technical, clinical and angiographic results were analyzed. Results: Thirty-six Surpass Evolve were successfully implanted in all subjects to treat 35 patients using an XT 27 ( 0.027') microcatheter supported by a Cathayst 5, 0.58 F distal access system and a proximal 0.88 F long sheath. No deployment failure in our series was observed. No intraprocedural morbidity or mortality was seen. No increase in the mRS until March 2020. Clinical and angiographic follow-ups are ongoing and will be completed and presented at the annual meeting. Conclusions: Our preliminary experience demonstrates good performance of the Surpass Evolve with no intraprocedural mortality and morbidity and no increase in mRS until the time of submission of this paper. The follow-ups are still in process and full results will be presented at the meeting. The technology is a more user-friendly technology due to the device characteristics with far easier advancement, the accuracy of placement and adjustment features. Disclosures: S. Derakhshani: None. J. Lynch: None. L. Kanagarajah: None.